2009
DOI: 10.1155/2009/147356
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms Modifying Oxidative Stress Are Associated with Disease Activity in Rheumatoid Arthritis Patients

Abstract: Abstract.Reactive oxygen and nitrogen species are involved in the pathology of rheumatoid arthritis (RA). Polymorphisms in genes coding for superoxide dismutases (SOD2 and SOD3), catalase (CAT), tumor necrosis factor-alpha (TNFA) and inducible NO synthase (NOS2A) may influence RA activity. We determined SOD2 Ala-9Val, SOD3 Arg213Gly, CAT C-262T, TNFA G-308A, TNFA C-857T and NOS2A (CCTTT)n polymorphisms in 327 RA patients. Carriers of CAT -262T and TNFA -308A allele had lower mean disease activity score of 28 j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…Superoxide dismutase (SOD) catalyses the dismutation of O 2 ⋅ -to H 2 O 2 and oxygen (O 2 ), while catalase (CAT) decomposes H 2 O 2 to water and oxygen. Single nucleotide polymorphisms (SNPs) of genes coding the antioxidant enzymes may alter enzyme structure, substrate specificity or activity and thus modify inter-individual variability in the defense capacity against oxidative stress [4]. The most extensively studied rs4880 (MnSOD Ala16Val) polymorphism of the manganese superoxide dismutase (MnSOD) gene is located at amino acid position 16 in the mitochondrial targeting sequence (MTS) resulting in the replacement of an alanine with a valine (Ala16Val).…”
Section: Original Papersmentioning
confidence: 99%
“…Superoxide dismutase (SOD) catalyses the dismutation of O 2 ⋅ -to H 2 O 2 and oxygen (O 2 ), while catalase (CAT) decomposes H 2 O 2 to water and oxygen. Single nucleotide polymorphisms (SNPs) of genes coding the antioxidant enzymes may alter enzyme structure, substrate specificity or activity and thus modify inter-individual variability in the defense capacity against oxidative stress [4]. The most extensively studied rs4880 (MnSOD Ala16Val) polymorphism of the manganese superoxide dismutase (MnSOD) gene is located at amino acid position 16 in the mitochondrial targeting sequence (MTS) resulting in the replacement of an alanine with a valine (Ala16Val).…”
Section: Original Papersmentioning
confidence: 99%
“…In contrast, Bohanec et al [14] provided evidence that patients with the GSTT1 null genotype had a higher risk for developing high activity RA than patients with GSTT1 genes present and that the GSTM1 and GSTP1 polymorphisms were not associated with the disease activity.…”
Section: Discussionmentioning
confidence: 92%
“…At present we know that chronic exposure to excess ROS may contribute to brain damage and pathophysiology of schizophrenia [1,2,11,12], CAT involved in detoxification of ROS [5][6][7][8][9][10], and C-262T polymorphism is associated with CAT activity [3,4]. Taken together, these findings sufficiently provide us with a theoretical ration to investigate the association between CAT C-262T polymorphism and susceptibility to schizophrenia.…”
Section: Introductionmentioning
confidence: 86%
“…Several studies indicated that the polymorphism of C-262T CAT is associated with some multifactorial diseases [5][6][7][8][9][10]. At present we know that chronic exposure to excess ROS may contribute to brain damage and pathophysiology of schizophrenia [1,2,11,12], CAT involved in detoxification of ROS [5][6][7][8][9][10], and C-262T polymorphism is associated with CAT activity [3,4].…”
Section: Introductionmentioning
confidence: 99%